The family man [videorecording (DVD)] - Ratner, Brett; Cage, Nicolas, 1965-; Leoni, Téa, 1966-; Piven, Jeremy; Sommer, M. Josef; Rubinek, Saul, 1948-; Cheadle, Don (Universal Studios, 2001)
Jack Campbell, a workaholic Wall Street exec, gets to see what his life might have been like if he'd stayed with his former sweetheart, Kate. Thirteen years after they split up, Jack falls asleep in his posh New York apartment, then awakens to find himself a family man, with his now-wife Kate, daughter Annie and new baby.